2015
DOI: 10.1016/j.vaccine.2014.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of IL-15 on the generation, maintenance and cytotoxic potential of adaptive cellular responses induced by DNA vaccination

Abstract: IL-15 is an important cytokine for the regulation of lymphocyte homeostasis. However, the role of IL-15 in the generation, maintenance and cytotoxic potential of antigen specific T cells is not fully understood. Because the route of antigenic delivery and the vaccine modality could influence the IL-15 requirement for mounting and preserving cytotoxic T cell responses, we have investigated the immunogenicity of DNA-based vaccines in IL-15 KO mice. DNA vaccination with SIV Gag induced antigen-specific CD4(+) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…A dose escalation trial in cART-treated HIV-infected patients showed that IL-7 was well-tolerated and could improve the available TCR repertoire, potentiate cytotoxic T-cell activity and restore CD4 + T-cell homeostasis [49, 50]. On the other hand, supplementation with IL-15 promoted the differentiation of central memory CD4 + T-cells into shorter-lived transitional or effector memory T CD4 + , which are crucial to immune control [51, 52]. Finally, IL-21 improved T-cell cytotoxicity as well as enhancing antibody production and not increasing viral load in chronically untreated SIV-infected macaques.…”
Section: Immunotherapy In the Disease Settingmentioning
confidence: 99%
“…A dose escalation trial in cART-treated HIV-infected patients showed that IL-7 was well-tolerated and could improve the available TCR repertoire, potentiate cytotoxic T-cell activity and restore CD4 + T-cell homeostasis [49, 50]. On the other hand, supplementation with IL-15 promoted the differentiation of central memory CD4 + T-cells into shorter-lived transitional or effector memory T CD4 + , which are crucial to immune control [51, 52]. Finally, IL-21 improved T-cell cytotoxicity as well as enhancing antibody production and not increasing viral load in chronically untreated SIV-infected macaques.…”
Section: Immunotherapy In the Disease Settingmentioning
confidence: 99%
“…The published data suggest a role for homeostatic cytokines, such as IL-7 and IL-15, in memory T and B cell survival (9). However, the absence of IL-7 or/and IL-15 only reduces, but not abrogates completely, the generation of the immune memory in different experimental models (911). From this, it appears that some memory cells can be generated and maintained in the absence of homeostatic cytokines.…”
Section: Introductionmentioning
confidence: 98%
“…Maintenance of effector/memory CD8 + T cells also requires IL‐7 . The cytokine IL‐15 can contribute to this process, and it is particularly important for the preservation of highly differentiated CD8 + effector T cells . DCs, monocytes (CD14 + ), CD34 + hematopoietic progenitor cells and BM stromal cells have been described to produce IL‐15 .…”
Section: Introductionmentioning
confidence: 99%